2007
DOI: 10.1243/09544119jeim288
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering of the synovial joint: The role of cell density

Abstract: The ultimate goal in the tissue engineering of the synovial joint is to fabricate biologically derived analogues that can replace severely degenerated or traumatized synovial joint components. A number of challenges must be addressed before reaching this ultimate goal. In this report, the relevance of cell seeding density in the synthesis of chondrogenic and osteogenic matrices from human mesenchymal stem cells is explored. Human mesenchymal stem cells (hMSCs) were differentiated into chondrogenic cells and os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…This range is arbitrarily chosen and could likely be expanded by increasing or decreasing the cell density in the hydrogel precursor solution. The ability to vary cell density is important in view of previous studies, which have shown that changes in cell density in 3-D PEG hydrogels strongly influence cell survival and differentiated function [44]. Herein we found that NIH-3T3 cell viability is improved after 7 days of culture at high cell seeding densities when compared with culture at lower seeding densities (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…This range is arbitrarily chosen and could likely be expanded by increasing or decreasing the cell density in the hydrogel precursor solution. The ability to vary cell density is important in view of previous studies, which have shown that changes in cell density in 3-D PEG hydrogels strongly influence cell survival and differentiated function [44]. Herein we found that NIH-3T3 cell viability is improved after 7 days of culture at high cell seeding densities when compared with culture at lower seeding densities (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…This would match well with data on the structural organization of cartilage tissue describing a cellular density of 24,000 cells/mm 3 at the articular surface decreasing 3.5-fold to about 7000 cells/mm 3 at the lower half of the upper radial zone 42 and with studies emphasizing high density to favor chondrogenesis. 43,44 Currently it is unclear whether application of even higher cell densities would give better results, and this might certainly be interesting to investigate in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest that a decline in the numbers, proliferation, or potential of stem cell populations in adult organs may contribute to characteristics of human aging, such as the decline in bone mass and age-related diseases including osteoarthritis and osteoporosis [16], [17]. In addition, although it has not been reported that a greater number of mesenchymal stem cells in the tissue increases its volume, Troken et al[18] suggested that higher mesenchymal stem cell densities yielded more marked matrix synthesis in vivo implantation. Mineral apposition is not attenuated by seeding hMSC-derived osteoblasts at a high density or in close proximity to each other.…”
Section: Discussionmentioning
confidence: 99%